Step
*
4
of Lemma
Taylor-remainder-as-integral
1. I : Interval
2. iproper(I)
3. a : ℝ
4. a ∈ I
5. b : ℝ
6. b ∈ I
7. [rmin(a;b), rmax(a;b)] ⊆ I 
8. n : ℤ
9. 0 < n
10. F : ℕ(n - 1) + 2 ⟶ I ⟶ℝ
11. x : ∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y)))
12. x1 : finite-deriv-seq(I;(n - 1) + 1;i,x.F i x)
13. x2 : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
14. y : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
15. x2 = y
⊢ ((F ((n - 1) + 1) x2/r((n - 1)!)) * b - y^n - 1) = ((F ((n - 1) + 1) y/r((n - 1)!)) * b - y^n - 1)
BY
{ (Subst' (n - 1) + 1 ~ n 0 THENA Auto) }
1
1. I : Interval
2. iproper(I)
3. a : ℝ
4. a ∈ I
5. b : ℝ
6. b ∈ I
7. [rmin(a;b), rmax(a;b)] ⊆ I 
8. n : ℤ
9. 0 < n
10. F : ℕ(n - 1) + 2 ⟶ I ⟶ℝ
11. x : ∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y)))
12. x1 : finite-deriv-seq(I;(n - 1) + 1;i,x.F i x)
13. x2 : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
14. y : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
15. x2 = y
⊢ ((F n x2/r((n - 1)!)) * b - y^n - 1) = ((F n y/r((n - 1)!)) * b - y^n - 1)
Latex:
Latex:
1.  I  :  Interval
2.  iproper(I)
3.  a  :  \mBbbR{}
4.  a  \mmember{}  I
5.  b  :  \mBbbR{}
6.  b  \mmember{}  I
7.  [rmin(a;b),  rmax(a;b)]  \msubseteq{}  I 
8.  n  :  \mBbbZ{}
9.  0  <  n
10.  F  :  \mBbbN{}(n  -  1)  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
11.  x  :  \mforall{}k:\mBbbN{}(n  -  1)  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y)))
12.  x1  :  finite-deriv-seq(I;(n  -  1)  +  1;i,x.F  i  x)
13.  x2  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
14.  y  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
15.  x2  =  y
\mvdash{}  ((F  ((n  -  1)  +  1)  x2/r((n  -  1)!))  *  b  -  y\^{}n  -  1)  =  ((F  ((n  -  1)  +  1)  y/r((n  -  1)!))  *  b  -  y\^{}n  -  1)
By
Latex:
(Subst'  (n  -  1)  +  1  \msim{}  n  0  THENA  Auto)
Home
Index